Mechanistic analysis for the origin of diverse diterpenes in Tripterygium wilfordii - Lichan Tu; Xinbo Cai; Yifeng Zhang; Yuru Tong; Jian Wang; Ping Su; Yun Lu; Tianyuan Hu; Yunfeng Luo; Xiaoyi Wu; Dan Li; Luqi Huang; et al. (Acta Pharmaceutica Sinica B, 2022)
Tripterygium wilfordii is a valuable medicinal plant rich in biologically active diterpenoids, but there are few studies on the origins of these diterpenoids in its secondary metabolism. Here, we identified three regions containing tandemly duplicated diterpene synthase genes on chromosomes (Chr) 17 and 21 of T. wilfordii and obtained 11 diterpene synthases with different functions. We further revealed that these diterpene synthases underwent duplication and rearrangement at approximately 2.3–23.7 million years ago (MYA) by whole-genome triplication (WGT), transposon mediation, and tandem duplication, followed by functional divergence. We first demonstrated that four key amino acids in the sequences of TwCPS3, TwCPS5, and TwCPS6 were altered during evolution, leading to their functional divergence and the formation of diterpene secondary metabolites. Then, we demonstrated that the functional divergence of three TwKSLs was driven by mutations in two key amino acids. Finally, we discovered the mechanisms of evolution and pseudogenization of miltiradiene synthases in T. wilfordii and elucidated that the new function in TwMS1/2 from the terpene synthase (TPS)-b subfamily was caused by progressive changes in multiple amino acids after the WGT event. Our results provide key evidence for the formation of diverse diterpenoids during the evolution of secondary metabolites in T. wilfordii.